10p-2p-9=39

Simple and best practice solution for 10p-2p-9=39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10p-2p-9=39 equation:


Simplifying
10p + -2p + -9 = 39

Reorder the terms:
-9 + 10p + -2p = 39

Combine like terms: 10p + -2p = 8p
-9 + 8p = 39

Solving
-9 + 8p = 39

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 8p = 39 + 9

Combine like terms: -9 + 9 = 0
0 + 8p = 39 + 9
8p = 39 + 9

Combine like terms: 39 + 9 = 48
8p = 48

Divide each side by '8'.
p = 6

Simplifying
p = 6

See similar equations:

| 4(2x-4)=9 | | 3(q)+(-1)(1-q)=(-4)q+2(1-q) | | x-21+x=47 | | P/5-4=6 | | -8w=2 | | 6x+10=6(x+3) | | 6x-12=20+4 | | 9(3y-6)-(8y+3)= | | y=-(4-x)(x+3) | | 6+4w=-2 | | x^2-2.1x+0.8=0 | | 22a-22=-4(1-4a) | | 8x-15+4=5x+6 | | X-5=0.4444X | | 17c/5 | | 3(4)-12-2=x | | 10-7x-11x+4= | | 2=9x+7 | | F(x)=6x^2-900 | | x+2sqrt(x+1)=7 | | Y=(4x^3)-(6x^2)-5 | | 9(2+x)-4x=x | | 43=4n-7 | | 84-19b+b^2=24 | | a-8=9a+7 | | (x^2-64/8x)•(2/8-x) | | 3/5u=9/5 | | (5x-7)-(2x-1)=0 | | 1x=4x-24 | | 5(3x-8)-5=5(x-4)+55 | | 5(1+c)=6(z+c) | | 10x-3=24 |

Equations solver categories